The hand that first held mine ebook A novel. - O'Farrell, Maggie (2011)
From the best-selling author of Hamnet and The Marriage Portrait comes a spellbinding novel of two women connected across fifty years by art, love, betrayals, secrets, and motherhood. "An exquisitely sensual tale of love, motherhood, and other forms of madness, The Hand That First Held Mine will unsettle, move, and haunt you." —Emma Donoghue, author of Room Lexie Sinclair is plotting an extraordinary life for herself. Hedged in by her parents' genteel country life, she plans her escape to London. There, she takes up with Innes Kent, a magazine editor who introduces her to the thrilling, underground world of bohemian, post-war Soho. She learns to be a reporter, to know art and artists, to embrace her life fully and with a deep love at the center of it. And when she finds herself pregnant, she doesn't hesitate to have the baby on her own. Later, in present-day London, a young painter named Elina dizzily navigates the first weeks of motherhood. She doesn't recognize herself: she finds herself walking outside with no shoes; she goes to the restaurant for lunch at nine in the morning; she can't recall the small matter of giving birth. But for her boyfriend, Ted, fatherhood is calling up lost memories, with images he cannot place. As Ted's memories become more disconcerting and more frequent, it seems that something might connect these two stories—these two women—something that becomes all the more heartbreaking and beautiful as they all hurtle toward its revelation. Praised by The Washington Post as a "breathtaking, heart-breaking creation," The Hand That First Held Mine is a gorgeous and tenderly wrought story about the ways in which love and beauty bind us together. It is a gorgeous inquiry into the ways we make and unmake our lives, who we know ourselves to be, and how even our most accidental legacies connect us.